Strategi Guru Menumbuhkan Sikap Toleransi Peserta Didik Beda Agama Di SMA Negeri 3 Tarutung - Erpinna Sipahutar; Debora Paulina Lumbantobing; Hotlinar Gultom; Arip Surpi Sitompul (Institut Agama Kristen Negeri Manado, 2023)
This study aims to obtain an objective and comprehensive picture of: a) How is the tolerance of students of different religions at SMA Negeri 3 Tarutung?; b) What is the teacher's strategy for fostering tolerance of students of different religions in SMA Negeri 3 Tarutung?; c) What are the factors that influence the tolerance attitude of students of different religions in SMA Negeri 3 Tarutung? This research is field research, which is looking for where the events that are the object of research take place, so as to get direct and up-to-date information about the relevant issues, as well as cross-checking of existing materials. Based on the results of the study, it can be concluded: 1) The attitude of tolerance among students of different religions, namely the role of Christian and Islamic Religious Education teachers, the role of schools, and the role of parents as facilitators for students to be tolerant; 2) The teacher's strategy in cultivating tolerance for Tarutung 3 State Senior High School students is to act as an educator for tolerance for students of different religions in the school environment; 3) The factors of tolerance of students of different religions are advice and enthusiasm from the teacher, parents of students, and friends of the students themselves.